Comparison of neural models, off-line and on-line learning algorithms for a benchmark problem - Ruano, Antonio (2013)
This papcr comparcs thc application of diffcrcnt ncural modcls-multilaycr pcrccptrons, radial basis functions and B-splincs - for a bcnchmark problem, and illustrates the applicability of a common learning algorithm for all models considered. The learning algorithm is employed both for off-line training and for on-line model adaptation. In the latter case. a sliding window of past learning data is employed.